Kinerja Konvolusi pada Sistem Amplify and Forward dengan Predistorsi dan Seleksi Relai - Annisa Anggun Puspitasari; Mareta Dwi Nor Habibah; Ziyadatus Shofiyah; Ida Anisah; Yoedy Moegiharto (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2022)
This paper evaluated the performance of the convolutional coding technique in a cooperative communication system using the amplify-and-forward (AF) protocol and applying a relay selection strategy by simulation. At the transmitter (source) side, a joint of peak average power ratio (PAPR) reduction techniques with selective mapping (SLM) schemes and the Hammerstein predistortion model was applied. The predistortion technique with the Rapp inverse model was applied at the relay. On the channel side, the relays were used as a virtual antenna, where relay usage in cooperative communication systems can be implemented for 4G or 5G networks in future research, even though it requires large bandwidth. Implementing the relay selection strategy can increase bandwidth efficiency because only the best relay will forward information from source to destination. The conventional relay selection strategy was used to evaluate the performance of the convolution coding in a multi-relay scheme by choosing the best relay considering the signal-to-noise ratio (SNR) value on the source to relay and relay to the destination channel. Only the best relay will forward the signal from source to destination using the AF protocol. System performance is expressed in bit error rate (BER) probability. The simulation results showed that the convolutional coding technique could improve system performance up to 16.59% with or without predistortion techniques. Then, the predistortion technique applied on the source and relay side generated the best performance, where the system performance could increase up to 34%. In addition, the implementation of the conventional relay selection strategy showed that the scheme with the most relays, which was six relays, could produce the best performance due to the increasing number of available paths.